Disability and Patient-Reported Satisfaction in Women with Idiopathic Intracranial Hypertension: A Comparative Study of Venous Sinus Stenting and Medical Management - Ortal Buhbut; Hadas Ben Assayag; Sapir Aharoni-Bar; Maor Epstein; Erez Tsumi; Tamir Regev; Anna Bunin; Asaf Honig; Bar O. Kotaro; Gal Ben Arie; Anat Horev (Diagnostics)
Objective: Patients with chronic idiopathic intracranial hypertension (IIH) commonly experience a high level of disability and low satisfaction with medical treatment. We aim to evaluate long-term functional improvement and patient satisfaction in IIH patients with similar symptoms by comparing venous sinus stenting (VSS) to standard medical therapy. Methods: We conducted a cross-sectional questionnaire study of 111 IIH patients, comparing 37 adult female patients who underwent venous sinus stenting with 74 patients treated medically. Propensity score matching was used to balance age and presence of papilledema at presentation between groups. Headache-related disability was evaluated using the Migraine Disability Assessment Scale (MIDAS), while general function and treatment satisfaction were assessed using custom questionnaires. Electronic medical records and the results of imaging upon diagnosis were reviewed retrospectively. Results: The stented group reported significantly better outcomes in physical well-being (median 4.0 vs. 1.0, p < 0.001), task completion (4.0 vs. 1.0, p < 0.001), work/school persistence (5.0 vs. 1.0, p < 0.001), and mental well-being (4.0 vs. 1.0, p < 0.001). Additionally, the stented group had a lower proportion of patients with severe MIDAS (MIDAS > 4, 24.3% vs. 47.9%, p = 0.017). Logistic regression suggested venous stenting as a protective factor against severe MIDAS scores (OR = 0.174, p = 0.004). Conclusion: Cerebral venous stenting in patients with IIH is associated with lower disability and higher patient satisfaction from medical treatment compared to those treated with medications only. These findings suggest that venous sinus stenting may be a valuable treatment option for selected IIH patients. However, larger prospective studies are needed to further validate our results.